Right inferior phrenic artery pseudoaneurysm after a laparoscopic gastrectomy: a case report - Kaoruko Funakoshi; Yuji Ishibashi; Shuntaro Yoshimura; Ryoto Yamazaki; Fumihiko Hatao; Yasuhiro Morita; Kazuhiro Imamura (Surgical Case Reports)
Abstract Background Ruptured pseudoaneurysms are a rare complication of gastrectomy, but when they do develop, they are often fatal. We presented herein the first report of a case of pseudoaneurysm arising from the right inferior phrenic artery (RIPA) after a laparoscopic gastrectomy. Case presentation A 61-year-old male patient underwent a laparoscopic distal gastrectomy and D1+ lymph node dissection with Roux-en-Y reconstruction for early gastric cancer. He was discharged on postoperative day (POD) 9 without any complications, such as anastomotic or pancreatic leakage. On POD 19, he was referred to the emergency room for upper abdominal pain. Enhanced abdominal computed tomography revealed a 60 × 70 mm hematoma, indicating intra-abdominal bleeding and a 10-mm pseudoaneurysm in the RIPA. Selective digital subtraction angiography confirmed the presence of a pseudoaneurysm in the RIPA, which was embolized using multiple microcoils. Thereafter, no clinical signs were observed, and the patient was discharged from the hospital 15 days after angiography without any recurrence of bleeding. We hypothesized that the cause of the pseudoaneurysm was mechanical vascular injury due to the thermal spread of the ultrasonically activated devices (USADs) during lymphatic node dissection. Conclusion Given the thermal spread of USADs, safe and appropriate lymph node dissection based on precise anatomical knowledge is crucial to preventing postoperative pseudoaneurysms.